The Politics of Children's Services Reform : Re-examining Two Decades of Policy Change - Purcell, Carl (Book collections on Project MUSE., 2020)
Drawing on unique access to prominent policy makers including ministers, senior civil servants, local authority directors, and the leaders of children's sector NGOs, Purcell re-examines two decades of children's services reform under both Labour and Conservative-led governments.He closely examines the origins of Labour's Every Child Matters programme, the Munro review and more recent Conservative reforms affecting child and family social workers to reassess the impact of high profile child abuse cases, including Victoria Climbie and Baby P, and reveal the party political drivers of successive reform.